The Importance of Prevention and Control of Coronovirus Disease (Covid-19) in Dental and Oral Hospital (Jurnal Ilmu Kesehatan Masyarakat, 2020)
Coronavirus has become certain threat toward dental and oral healthcare, therefore Dental and Oral Hospital as healthcare and academic facilities in dentistry should notice to conduct Coronavirus (Covid-19) prevention and control efforts. The article aims to analyze the importance of policies on Coronavirus (Covid-19) prevention and control in Dental and Oral Hospital. The Literature Review used in the article was Systematic Literature review method by analyzing 429 arcticles in the search engine of WHO scientific articles related to the key words and obtained 13 articles which were collected as the literature study materials which were related to the theme of the implementation of Coronavirus (Covid-19) prevention and control policies. Based on the result of the study it may get conlcuded that the Management Role of Dental and Oral Hospital as the designer and the instigator of healthcare service and academic activities implementation is very crucial. Commitment of the stakeholders should be performed yet need to consider the guidelines aspect which is suggested and used from various references as well as the central government’s policies to apply effective Coronavirus Disease (Covid-19) prevention and control. In the prevention and control related to dentistry academic activities it requires an available smart gadget and application to enable students listening and reviewing lectures at anywhere and anytime possible. Therefore, the implementation of Coronavirus Disease (Covid-19) prevention and control may run effectively and efficiently.